Psikoedukasi Perilaku Seksual Menyimpang pada Siswa Sekolah Menengah Keatas - Miqdad Daly Ahmad; Diah Liandary Nurmaulida; Rahmita Laily Muhtadini; Udi Roshida Hijriyanti (Yayasan Literasi Sains Indonesia, 2026)
This community service program aims to enhance adolescents’ knowledge of deviant sexual behavior through school based psychoeducation as a preventive measure against rising risky sexual behaviors in Indonesia. Adolescence is a transitional phase in human development that is particularly susceptible to environmental influences, such as peers and digital media, making systematic and practical educational interventions essential. The program was implemented at SMA Muhammadiyah Malang 1 and involved 45 students as participants. The method employed was psychoeducation delivered through interactive lectures, group discussions, and case studies relevant to adolescents’ daily lives. The program evaluation used a one-group pretest–posttest design to measure changes in participants’ knowledge before and after the intervention. The instrument used was a multiple-choice test, and data were analyzed using the Wilcoxon signed-rank test. The results showed a significant increase between pretest and posttest scores (W = 94.0; p = 0.004), indicating that psychoeducation was effective in enhancing students’ understanding of deviant sexual behavior. Additionally, the increase in mean and median scores, along with the reduction in score variability, suggests that participants’ understanding became more evenly distributed after the program. Therefore, psychoeducation can serve as an effective preventive strategy to enhance knowledge and foster more adaptive attitudes among adolescents. This program is expected to serve as an intervention model that can be more widely implemented in educational settings, although it is limited by the small number of participants and the absence of a comparison group.